Preclinical detection of Alzheimer's disease: hippocampal shape and volume predict dementia onset in the elderly - Csernansky, J.G.; Wang, L.; Swank, J.; Miller, J.P.; Gado, M.; McKeel, D.; Miller, M.I.; Morris, J.C. (NeuroImage (Orlando, Fla.), 2005)
Structural deformity of the hippocampus is characteristic of individuals with very mild and mild forms of dementia of the Alzheimer type (DAT). The purpose of this study was to determine whether a similar deformity of the hippocampus can predict the onset of dementia in nondemented elders. Using high dimensional diffeomorphic transformations of a neuroanatomical template, hippocampal volumes and surfaces were defined in 49 nondemented elders; the hippocampal surface was subsequently partitioned into three zones (i.e., lateral, superior and inferior-medial), which were proximal to the underlying CA1 subfield, CA2–4 subfields plus dentate gyrus, and subiculum, respectively. Annual clinical assessments using the Clinical Dementia Rating scale (CDR), where CDR 0 indicates no dementia and CDR 0.5 indicates very mild dementia, were then performed for a mean of 4.9 years (range 0.9–7.1 years) to monitor subjects who converted from CDR 0 to CDR 0.5. Inward variation of the lateral zone and left hippocampal volume significantly predicted conversion to CDR 0.5 in separate Cox proportional hazards models. When hippocampal surface variation and volume were included in a single model, inward variation of the lateral zone of the left hippocampal surface was selected as the only significant predictor of conversion. The pattern of hippocampal surface deformation observed in nondemented subjects who later converted to CDR 0.5 was similar to the pattern of hippocampal surface deformation previously observed to discriminate subjects with very mild DAT and nondemented subjects. These results suggest that inward deformation of the left hippocampal surface in a zone corresponding to the CA1 subfield is an early predictor of the onset of DAT in nondemented elderly subjects.